2022
DOI: 10.3390/math10040670
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Brucellosis Disease Incorporating Age of Infection and Waning Immunity

Abstract: This paper proposes a model for brucellosis transmission. The model takes into account the age of infection and waning immunity, that is, the progressive loss of immunity after recovery. Three routes of transmissions are considered: vertical transmission, and both direct and indirect routes of horizontal transmission. According to the well-posedness results, we provide explicit formulas for the equilibria. Next, we derive the basic reproduction number R0 and prove some stability results depending on the basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Let (S 0 , V 0 , e 0 (τ), I 0 , R 0 ) ∈ ∂B, and we have (e 0 (τ), I 0 , R 0 ) ∈ ∂ B. Then, the following system is obtained: (19) which is subject to the boundary…”
Section: Uniform Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Let (S 0 , V 0 , e 0 (τ), I 0 , R 0 ) ∈ ∂B, and we have (e 0 (τ), I 0 , R 0 ) ∈ ∂ B. Then, the following system is obtained: (19) which is subject to the boundary…”
Section: Uniform Persistencementioning
confidence: 99%
“…Dai and Zhang [18] claimed that the incidence of eating disorders could be lowered if people continued their education. Kenne et al [19] demonstrated that birth rates directly affected the stability of diseases and that changing certain parameters triggered periodic epidemics, making it difficult to eradicate them from the population. Li and Wang [20] held that in order to effectively control infectious diseases, it was crucial to recruit few susceptible people, restrict travel, and ban large gatherings of people, in addition to vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis in the exposure period is hardly detected, and animals in this period can also infect susceptible animal and humans. Hence, we ignored the exposed/latent period in both human and animal population (see for example [15,20,21,22]);…”
Section: An Autonomous Brucellosis Modelmentioning
confidence: 99%
“…Several mathematical models have been proposed to study the dynamics of brucellosis outbreaks [5,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Undeniably, these studies have produced many useful results and improved the existing knowledge on brucellosis dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models have proved to be essential guiding tools for epidemiologists, biologists as well as policy makers (See for example [10,11,12,13,14,15,16,17,18]). Recently, modelling the transmission dynamics of brucellosis, is one of the most common global zoonoses [19], has been an interesting topic for a number of researchers (see, for example [6,18,20,21,22,23,24,25,26,27]).…”
Section: Introductionmentioning
confidence: 99%